Validation of the attitudes to patient safety questionnaire for nursing students in the Spanish context - Águeda Cervera-Gasch; Víctor M González-Chordá; Fred Gustavo Manrique-Abril; Laura Andreu-Pejo; María Jesús Valero-Chillerón; Desirée Mena-Tudela (BMC, 2021)
Abstract Background There are different instruments to assess the attitudes of nursing students towards patient safety. However, no questionnaire validated in Spanish with this objective was identified. The objective of this study was to validate the Attitudes to Patient Safety (APS) questionnaire for nursing students in Spain and to study the attitudes towards patient safety of nursing students at the Universitat Jaume I (Spain). Design Cross-sectional psychometric study developed in a sample of 177 undergraduate nursing students. The study was carried out in the second semester of 2016. Methods First, a nominal group was created to perform cross-cultural adaptation and determine content validity of the Attitude to Patient Safety Questionnaire (APQS-III). Second, a cross-sectional study was conducted to determine the psychometric properties of the questionnaire and to study nursing student attitudes towards patient safety. Results Exploratory factorial analysis explained 53.82 % of the variance, with good internal consistency (α = 0.808), and confirmatory factor analysis indicate an adequate fit between the model and the data (χ2 = 366; p < 0.001; χ2/df = 1.886; RMSEA = 0.07; IC95 %=0.059-0.081; CFI = 0.885). Intra-observer reliability was good (ICC = 0.792, p < 0.001). The mean overall score of the questionnaire was 3.92 (95 % CI = 3.88-4.03). Significant differences were observed regarding whether the students had completed a clinical practicum (p = 0.012) and the academic year (p = 0.25). Conclusions The psychometric properties of the APS questionnaire adapted for Spanish nursing students are adequate. Students show an adequate attitude towards patient safety; however, it is necessary to develop a strategy to guarantee the acquisition of competency for patient safety as well as to design and evaluate specific educational interventions.